Alternate nostril breathing (Nadi-Shodhana Pranayama) and its impact on perceived stress and hearing threshold among medical students; a prospective study - Smitha Nagendrappa; Sudhir Goppenahalli Kumaraswamy; Vinay Hosagavi Ramalingaiah (Asian Journal of Medical Sciences, 2025)
Background: Medical students often experience significant psychological stress, which can negatively impact their academic performance, cognitive functions, and overall well-being. Psychological/emotional stress can also affect hearing if severe or if it lasts long enough. Amongst stress reduction strategies, meditation techniques are found to be helpful. Aims and Objectives: This study aimed to assess the effect of alternate nostril breathing (Nadi-Shodhana Pranayama) on perceived stress and auditory thresholds (AT) among medical students. Materials and Methods: Following institutional ethics committee approval, a sample of 60 consenting students aged 18–26 years participated in a 3-month intervention, where they practiced pranayama for 15–20 min, 5 days a week. Baseline and post-intervention data were collected using the perceived stress scale (PSS) and pure tone audiometry. Results: The results demonstrated a statistically significant reduction in PSS scores (P<0.001), indicating decreased stress levels. In addition, ATs in both ears improved, with a more pronounced change observed in the left ear (P<0.001). These findings suggest that pranayama not only reduces psychological stress but also enhances auditory perception, possibly through the regulation of stress hormones and improved inner ear functioning. Conclusion: The study supports the use of pranayama as a simple, non-invasive intervention to reduce stress which tends to improve cognitive performance in medical students, contributing to better academic outcomes and overall well-being. Further research is warranted to explore long-term benefits and potential mechanisms behind the observed improvements in auditory function and stress resilience.